Anatomical Variants of the Placenta in Sudanese and their Relation to the Neonatal Outcome - Ahmed Abdelrahman NuggedAlla Motaz; Seddeg Abdulghani Yasser; Ahmed Mirghani Osman Omer; ElHadi Babikir Haydar (International Journal of Human Anatomy, 2020)
Background In recent years great attention has been focused on the structural and histological structures of the placenta and the umbilical cord due to their vital roles in fetal development and neonatal survival. While extensive studies have been documented in this area in the developed world, there is very little published information about the morphological variations that occur in human placenta in Sudan. Therefore, this study was designed to evaluate the structural variations in placental indices and its relation to neonatal outcome. Methods A prospective hospital - based study conducted in Wad Madani Maternity Teaching Hospital Department of Obstetrics and Gynecology between July 2014 and March 2018. Results Mean placental indices for weight, diameter and thickness were 515.51 g, 18.80 cm and 2.43 cm respectively. The mean neonatal indices were 2.95 kg, 33.19 cm and 44.42 cm for weight, head circumference and length respectively. Neonatal weight correlated significantly with placental weight, neonatal length and neonatal head circumference (P < 0.000). On the contrary, neonatal weight had no significant correlation with placental thickness and diameter Conclusion In this study, there was a strong relationship between the placenta and the fetus suggesting that the well-being of the fetus is highly dependent on the placenta since it serves as a link between the mother and the fetus.
Keywords: Placenta